Spinoza's authority. - Kordela, Aglaia Kiarina, 1963-; Vardoulakis, Dimitris (Bloomsbury studies in continental philosophy., 2018)
"Spinoza's political thought has been subject to a significant revival of interest in recent years. As a response to difficult times, students and scholars have returned to this founding figure of modern philosophy as a means to help reinterpret and rethink the political present. Spinoza's Authority Volume I: Resistance and Power in Ethics makes a significant contribution to this ongoing reception and utilization of Spinoza's political thought by focusing on his posthumously published Ethics. By taking the concept of authority as an original framework, this books asks: How is authority related to ethics, ontology, and epistemology? What are the social, historical and representational processes that produce authority and resistance? And what are the conditions of effective resistance? Spinoza's Authority features a roster of internationally established theorists of Spinoza's work, and covers key elements of Spinoza's political philosophy, including: questions of authority, the resistance to authority, sovereign power, democratic control, and the role of Spinoza's "multitudes"."--Bloomsbury Publishing